Annual and seasonal variation of tick-borne encephalitis virus (TBEV) prevalence in ticks in selected hot spot areas in Germany using a nRT-PCR: results from 1997 and 1998 - Süss, Jochen; Schrader, Christina; Abel, Ulrich; Voigt, Wolf P.; Schosser, Rudolf (Zentralblatt für Bakteriologie, 1999)
The prevalence of tick-borne encephalitis virus (TBEV) in Ixodes ricinus tick populations in endemic areas of Germany with the highest TBE risk is unknown. Annual and seasonal differences in TBEV prevalence have also not been studied. Against this background, in May 1997 we started a systematic virus surveillance programme in ticks collected in locations known to have a high incidence of autochthonous TBE cases. These were 5 locations in Baden-Württemberg (Black Forest) and 8 locations in Bavaria (surrounding Passau). Field-collected ticks were randomly assigned to pools of 10 adults or 20 nymphs, respectively. The tick pools were tested for the presence of TBEV-RNA using a newly developed, sensitive nested reverse transcriptase polymerase chain reaction assay (nRTPCR). The primer pairs were selected from the 5′-terminal noncoding region, a highly conserved part of the virus. The specificity was tested by computer homology searches of sequences, as well as by sequencing of the first and the second amplificates, by Southern blot hybridisation with a DIG-labelled oligonucleotide probe, and by restriction enzyme analysis. The method has proved to be very sensitive, with a detection limit of 20 fg of TBEV RNA per PCR run, or a single positive tick. Based on biostatistical considerations a sample size of at least 1000 ticks per estimation point was chosen. The estimated TBEV prevalence and confidence intervals (CI) were calculated from the nRT-PCR results of pooled samples (10 adults or 20 nymphs) using appropriate formulae for pooled testing. In order to identify the estimated TBEV prevalence as well as to assess the influence of annual and seasonal factors on TBEV prevalence, ticks were sampled twice a year (May and September) in 1997 and 1998 at exactly identical sites. These sites were selected because they were known to have had the highest incidence of autochthonous TBE cases during the previous 10 years. On sampling days, relevant local meteorological data were also noted. In total, 8500 I. ricinus ticks were investigated in this study, 4270 (3540 nymphs, 730 adults) from the Black Forest habitats, and 4230 (3680 nymphs, 550 adults) from the Bavarian locations. In the foci near Freiburg (Black Forest), the estimated virus prevalence was relatively high in the whole tick population, during 1997 with only slight seasonal differences [3.4% (confidence interval, CI, 2.3-4.8%) in May and 2.9% (CI 1.7-4.5%) in September]. In contrast, in 1998, in the same foci the estimated TBEV prevalence was considerably lower [1.1%(CI 0.5-2.0%) in May and 0.6%(CI 0.2-1.4%) in September]. Thus, while the seasonal differences again remained low, the annual variation was marked. In the Bavarian foci in 1997, the estimated virus prevalence of the whole tick population studied was lower than in the Black Forest foci and the seasonal fluctuations were low: in May 1997 0.9% (CI 0.4-1.8%) of the ticks were positive, in September 1.1% (CI 0.5-1.9%). In 1998, in May 2.0% (CI 1.1-3.3%) of the ticks were positive, and in September 1.1% (CI 0.5-2.1%). For the whole study period, every 50th to 100th I. ricinus nymph or adult in the Passau region was calculated to give a positive signal in the nRT-PCR. The TBEV prevalence data indicate that residents and visitors of areas in Germany known for high endemic activity take a significant risk of contracting TBEV infection, if bitten by ticks. In addition, the data suggest that annual fluctuations may exist in the whole tick population studied. Seasonal fluctuations of the virus prevalence in ticks were small.
Gesehen am 14.04.2021